Live Streaming Commerce as a Digital Marketing Innovation: A Conceptual Review of the Integration of the Stimulus Organism Response (SOR) Model and Corporate Strategic Capabilities - Mimanda, Arika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid development of digital technology has driven a marketing paradigm shift towards a more interactive and immersive model, with Live Streaming Commerce emerging as a key innovation in the modern e-commerce landscape (Zhou et al., 2021). This article aims to conceptually examine the role of live streaming as a strategic intervention in enhancing the shopping experience and driving consumer purchasing decisions, while also analyzing the organizational capabilities that support the successful adoption of this innovation. This study uses a conceptual approach through narrative synthesis from various literatures. This approach integrates the Stimulus Organism Response (SOR) framework with supporting theories such as Flow Theory (Csikszentmihalyi, 1990) and Experiential Marketing (Schmitt, 1999), and incorporates the perspective of the company's strategic capabilities. Using the Stimulus Organism Response (SOR) framework, this study explains that live streaming elements such as interactivity, broadcaster appeal, and content authenticity function as stimuli that influence the internal psychological state of consumers (organisms). These internal conditions include the formation of trust, social presence, and the creation of immersive experiences (purchase experiences) that engage consumers in the flow experience (Csikszentmihalyi, 1990; Lu et al., 2021). Furthermore, the success of this intervention requires support from the company's strategic capabilities. Live streaming innovation is driven by a company's market orientation and technology orientation (Gatignon & Xuereb, 1997), as well as a differentiation strategy through its unique features (Dickson & Ginter, 1987). Conceptual results indicate that the integration of Stimulus Organism Response (SOR) behavioral mechanisms and strategic capabilities drives a positive response in the form of purchase intention and enables companies to achieve a strategic customer-profit trade-off (Carson et al., 1998; Zhang et al., 2022). This article provides a theoretical contribution by bridging the Stimulus Organism Response (SOR) literature with the strategic innovation literature, and provides practical implications for e-commerce players in designing sustainable and competitive live streaming strategies.